Tactics of Antibacterial Treatment of the Recurrent Bronchitis in Children - G.O. Lezhenko; O.Ye. Pashkova; L.I. Pantyushenko (Zaslavsky O.Yu., 2012)
Analysis of efficiency of oral administration of Cefutil (cefuroximum axetil) antibiotic in treatment of reccurent bronchitis in children was carried out in this work. It is shown that Cefutil is an effective and safe medication and can be recommended as agent of choice in treatment of recurrent bronchitis in children with signs of bacterial infection.